Tahlil Kitab al-Lughah al-‘Arabiyyah li al-Madrasah al-‘Aliyah ‘ala Mandzur ‘Ali Muhammad al-Qasimi - Panagara, Fathi Hisyam; Amzaludin, Amzaludin; Fuadi, Abdul Hafizh Nur; Annisa, Maryam Nur; Al Farizi, Salman (Institut Agama Islam Negeri Curup, 2023)
This research aims to analyze the suitability of the Arabic language textbook for the eleventh grade, issued by the Ministry of Religious Affairs in its first edition in 2020, to determine whether the prescribed book aligns with the criteria of a textbook according to the theory of Ali Muhammad Al-Qasimy in developing teaching components for Arabic language instruction for non-native speakers. This textbook is selected because its implementation is still relatively new, and there are ongoing issues, such as using highly advanced reading texts. This research was conducted using a qualitative approach and the desk research method. A content analysis technique was employed to analyze the data. Primary data were collected by documenting content from the